Źródła sukcesu e-biznesu w komunikacji z klientem: The sources of e-business success in communication with the client - Zalewska-Turzyńska, Magdalena (Management and Administration Journal, 2021)
The success of an organization can be obtained in many fields. The purpose of this article is to trace the "classical" measures of organization success in a chronological order, and on this background to present the concept of company success sources identification located on the communication basis. Introduction of the concept and performed analysis is presented. The study area was limited to organizations operating in the virtual space and communications between businesses and e-customers.